REPRESENTATION OF YOUNG MALAY MUSLIM OPTIMISM IN HOORE! HOORE! (2012) AND ADIWIRAKU (2017) (Journal of Creative Industry and Sustainable Culture, 2022)
Narrative of Teen Films should be geared towards maturing, how to identify a problem, character and about future dreams as well as about the identification of teenager and the twists and turns of life, which is their contradiction and dilemma in the increasingly challenging social life. That way, teenagers can identify and be motivated to deal with the issue well after watching. The purpose of this study is to analyze and parse as well as to formulate the representation of Malay Muslim Youth optimism in Hoore! Hoore! (2012) and Adiwiraku(2017) films, based of five indicators of optimism according and optimism from Islamic perspective by Imam Al Ghazali exist in the narratives of both study films through character and the character of Malay Muslim teenagers. In this study, the author uses a qualitative approach with document analysis techniques and descriptive discussion on the optimistic attitude of Young Malay Muslim through teenage characters until the existence of optimism in both films. As a result, this study concludes that the indicator of optimism has been inserted and featured in both films effectively. Also, both films have presented and proved that the importance of Muslim Malay youth should have the knowledge, practices and beliefs of Islam in the ambitions, dreams and success in life.